Growth Performance of Poecilia reticulata and Betta splendens in Varying Water Hardness Treatments - Abarna, A.; Patrick, A.E.S.; Jayawardena, U.A. (University of Jaffna, 2018)
Vavuniya district in Sri Lanka experiences heavy water hardness levels in the underground aquifers, severely affecting the human health. However, there is a scarcity of research work on the effect of water hardness on aquatic animals in the area. Thus, the effect of water hardness on growth of aquarium fishes like Poecilia reticulata (Ovo-viviparous) and Betta splendens (Oviparous) were examined at 150 (control), 320, 540 and 900 mg/L CaCO3 in semi natural aquaria with 3 replicates. Higher level of hardness (900 mg/L) favoured the growth performance of P. reticulata than the B. splendens. Weight increment of P. reticulata showed significant difference (p = 0.005) between control and treatments. Length increment of P. reticulata also showed significantly higher value (p = 0.009) at 900 mg/L than other setups. The maximum weight was 0.89 ± 0.107 g and maximum length was 3.49 ± 0.024cm at the highest water hardness treatment. Maximum larval growth performance of P. reticulata by means of length was 21.83 ± 0.016 mm at 900 mg/L CaCO3. Final length of B. splendens larvae did not show significant difference (p = 0.228) among the water hardness setups, even though better growth (9.67 ± 0.577 mm) was obtained from 320 mg/L CaCO3. Thus, hard water environment (900 mg/L) appears to support the growth performance of P. reticulata larvae and adults than B. splendens. As higher water hardness is found in Vavuniya, it may provide better conditions for growing of P. reticulata to get optimal benefits from aquarium trade.
Keywords: Hardness; Growth performance; Aquarium fish